THE INFLUENCE OF ETHICS CODE TO SERVICE QUALITY AND WORK MOTIVATION OF SOCIAL ASISITENCES OF ‘’HOPE FAMILY PROGRAM-PKH’’ DURING PANDEMIC PERIOD IN CIANJUR REGENCY, WEST JAVA - PIPIT FITRIANTI; ERRY SUNARYA; R.DENI MUHAMMAD DANIAL (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The purpose of this study was to determine how much influence the PKH Human Resources Ethical Codes on the quality of services provided and work motivation from the encouragement of the ethical codes. The method used is associative research method with a quantitative approach. The object of research that was sampled in this study was 84 Pendamping Sosial PKH using the proportional stratified random sampling technique. The techniques used in data collection are questionnaires, participatory observation and documentation studies. The results of the study on the Effect of the Ethical Codes on Service Quality and Work Motivation of Pendamping Sosial PKH During the Covid-19 Pandemic in Cianjur City, were declared to have a significant positive effect or high influence so that when Service Quality and Work Motivation increased, the Ethical Codes would also increase by one point . Based on the results of the research findings, the authors suggest that the PKH Human Resources Ethical Codes must continue to be improved in its application in order to trigger an increase in service quality and work motivation of Pendamping Sosial PKH in providing services to beneficiaries so that this good application does not only occur during the Covid-19 pandemic. , however, is expected to continue to increase under any circumstances.